The impact of environmental quality components on enhancing social health: a case study on residential complexes of Ardabil city - Maleka Negari; Javad Javan Majidi; Elham Alavizadeh (Social Determinants of Health, 2025)
Background: Nowadays, in the evaluation of urban quality, urbanization is considered as one of the key factors affecting individual and social health. In this regard, just as human health is largely influenced by city programs and goals, urban life also depends on improving the overall quality of health. Therefore, attention must be paid to environmental quality and the enhancement of social health within residential complexes.